Integrating Faith and Green Practices: Religiosity as a Mediator Between Eco-Competence and Sustainability Performance in Indonesia’s Batik SMEs - Siti Aminah Chaniago; Susminingsih Susminingsih; Muhammad Nasrullah; Junaeti Junaeti; Ahmad Rosyid (Journal of Management and Entrepreneurship Research, 2026)
Objective: The preservation of Indonesia’s batik industry, an esteemed UNESCO cultural heritage, is currently threatened by escalating environmental degradation and criticism over toxic chemical discharge. Grounded in the Resource-Based View (RBV), this research explores how Eco-Competence—encapsulating environmental literacy, ethics, and waste mitigation skills—shapes Sustainability Performance. A central focus is placed on the knowledge-action gap, positioning Religiosity as a vital psychological bridge between technical aptitude and genuine green implementation. Research Design & Methods: This study applied a quantitative method through a survey involving 225 employees from three- to five-star green hotels located in Bandung and Jakarta. The collected data were subsequently analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Findings: The results reveal that green mindfulness positively influences employee green performance both directly and indirectly through the mediating roles of green human capital and green adaptive ability. In addition, green psychological climate strengthens the relationships between green mindfulness and the three related green outcomes. Implications & Recommendations: These findings imply that green mindfulness functions not only at the individual level but also through the influence of the organizational climate. Therefore, hotels should embed green mindfulness into HR practices (e.g., training, performance management) while simultaneously fostering a supportive green psychological climate to maximize employee green performance. Contribution & Value Added: This study contributes to the existing literature by broadening the Green Human Resource Management (GHRM) framework through the incorporation of the Ability–Motivation–Opportunity (AMO) theory. The findings demonstrate the role of green mindfulness as a foundational psychological resource that activates green competencies and adaptive capacity in organizations.